Comparing British and American conservatisms through the prism of African development. Issue 4 (2nd October 2017) - Andreasson, Stefan
ABSTRACT: Conservatism and conservative party politics in Britain and America is associated with neo-colonial attitudes, including pursuit of national interests ahead of post-colonial development. Based on interviews conducted in Washington and London with actors involved with African development, this article examines comparative shifts in conservatives' engagements from the late Cold War era to the G. W. Bush and Cameron governments. Greater ideological heterogeneity and distinctiveness among American conservative interests groups, combined with a bureaucratic environment in the US allowing more direct channels for ideological input into policy, results in a more clearly conservative stamp on Africa policy in the US than in Britain where ideological lines on development have become more blurred since the 1997 New Labour election victory and the creation of the Department for International Development.